PENGUATAN PROFIL PELAJAR PANCASILA SEBAGAI STRATEGI PENDIDIKAN KARAKTER DI SEKOLAH DASAR - Sri Dewi br Mangunsong; Kristi Handayani Larosa; Weni Sarbaini; Nurhayati Nurhayati; Sri widiya Astuti Telaumbanua (STKIP Subang, 2026)
This study aims to analyze the strengthening of character education through the implementation of Pancasila Student Profile values in the learning process in elementary schools. The background of this study is based on the importance of developing students' character in line with Pancasila values in learning activities. Character education is an important aspect in shaping students who have a sense of responsibility, the ability to work together, and the ability to think critically in facing various learning problems. This study uses a qualitative descriptive approach by analyzing learning activities that integrate the values of mutual cooperation, independence, critical thinking, and creativity. Data collection techniques were carried out through observation, documentation, and analysis of learning activities carried out in elementary schools. The results show that integrating Pancasila Student Profile values into learning has a positive impact on students' character development. Students show improvement in their ability to work together in group activities, independence in completing tasks, and critical and creative thinking skills in solving learning problems. In addition, learning that is designed collaboratively and contextually is able to create a more meaningful learning experience for students. Thus, the implementation of the Pancasila Student Profile can be an effective strategy in strengthening character education in elementary schools.